التطوير الجمركي وأثره على التسهيل التجاري - حالة الجزائر - بورويس, عبد العالي (جامعة الوادي - University of Eloued, 2023)
تتناول هذه الورقة البحثية موضوع تطوير إدارة الجمارك والعمل الجمركي في الجزائر، باعتبار أن تنفيذ برامج الإصلاح والتحديث أداة مهمة لتجسيد أحكام وبنود الاتفاقيات الدولية الخاصة بالقضايا الجمركية. وتمكن إدارة الجمارك من تأدية أدوار اقتصادية جديدة، بخلاف الدور الجبائي التقليدي. بناء عليه، تهدف هذه الورقة إلى الكشف عن استراتيجية تطوير الإدارة والعمل الجمركي التي تخص جوانب متعددة كالبيئة التشريعية والقانونية، وتبسيط نظم العمل والإجراءات الجمركية، واعتماد آلية الرقابة وإدارة المخاطر، وتطوير نزاهة العنصر البشري، ونظام الجمركة الآلية للبضائع. ونستخلص في الأخير النتائج العامة للتطوير الجمركي، والأثر الذي يحدثه على التسهيل التجاري. بإبراز أثر التطوير على تخفيف وتبسيط الإجراءات الجمركية، من خلال قياس معدل المراقبة الفعلية للبضائع، ومعدل الإفراج الجمركي، إضافة إلى أثره على الإيرادات الجمركية التي تقوم بها إدارة الجمارك. This research paper deals with the issue of developing administration and customs work in Algeria, given that the implementation of reform and modernization programs is an important tool for embodying the provisions of international agreements on customs issues. And it enables the customs administration to play new economic roles in contrast to the traditional fiscal role. Accordingly, this paper aims to reveal the strategy of developing administration and customs work that pertain to multiple aspects such as simplifying work systems and customs procedures, and the automated customs system for goods. Finally, we arrive at the conclusion of the general results of the customs development, and the impact it has on trade facilitation, by highlighting the impact of development on reducing and simplifying customs procedures by measuring the rate of physical examination of goods, the rate of customs release, in addition to its impact on customs revenues collected by the Customs Department.
Customs development and its impact on trade facilitation – case of Algeria
مقال
Keywords: الإجراءات الجمركية، التسهيل التجاري، الإفراج الجمركي، الإيرادات الجمركية، إدارة الجمارك.: Customs procedures; Commercial facility; Customs release; Customs revenue; Customs department.